1,n-Metal Migrations Mediated by 3d Transition Metals - Fujii, Ikuya; Shintani, Ryo (Synthesis, 2026)
Remote functionalization of unactivated sites remains a major challenge in transition-metal-catalyzed synthesis. This short review summarizes recent advances in through-space 1,n-metal migration reactions mediated by 3d transition metals, including Cr, Fe, Co, Ni, and Cu. These transformations enable site-selective bond formation at otherwise inaccessible positions and offer sustainable alternatives to conventional cross-coupling strategies. Mechanistic aspects such as ligand-controlled migration, σ-bond metathesis, isotope-labeling studies, and computational insights are highlighted to illustrate how regio- and stereoselectivity are achieved. Collectively, 3d metal-mediated 1,n-migration reactions provide a versatile platform for remote functionalization and open new avenues for reaction design in modern organic synthesis.
Keywords: Metal migration; 3d transition metals; Remote C–H activation; Organometallic chemistry; C–Si activation; C–B activation